Role of fragmented QRS and Shanghai score system in recurrence of ventricular fibrillation in patients with early repolarization syndrome - Keisuke Yonezu (Wiley, 2021)
Abstract Background The Shanghai Score System, which weighs electrocardiogram (ECG) findings reflecting repolarization abnormalities, has been proposed for diagnosis of early repolarization syndrome (ERS). However, recent studies have suggested the involvement of depolarization abnormalities in some ERS patients. The aim of this study was to validate the Shanghai Score System in predicting the recurrence of ventricular fibrillation (VF) in ERS patients. The predictive value of fragmented QRS (fQRS) was also investigated. Methods Fifteen consecutive ERS patients (14 males, median age of 47 years) with a history of VF were retrospectively reviewed. The Shanghai Score System points were calculated, and the presence of fQRS was evaluated. Results During the median follow‐up period of 79.2 months, five patients experienced VF recurrence. In the VF recurrence group, two patients showed augmented amplitude of J waves with horizontal ST‐segment, while the other three patients had dynamic changes in J‐wave amplitude. The Shanghai Score System points in the VF recurrence group were higher than those in the VF non‐recurrence group (6.5 [range: 5.8–6.8] vs. 4.5 [range: 4.0–4.5], p = 0.002). The presence of fQRS on standard 12‐lead ECG was more frequently observed in the VF recurrence group compared with the non‐recurrence group (100% vs. 10%, p = 0.002). Conclusions The present study demonstrated that the Shanghai Score System could effectively identify ERS patients at high risk for VF recurrence. The results also suggested that the presence of fQRS, a marker of depolarization abnormalities, may be useful for predicting VF recurrence in ERS patients.